Canira Malolo: An Alternative Treatment for Striae Gravidarum in Postpartum Mothers - A Pre-Experimental Study - Dina Mariana; Rizki Dyah Haninggar; Nurdiana Nurdiana; Arwinda Dwi Saputri; Nurul Zamzani MD; Al Madanyah; Hasnaria Hasnaria; Sri Armalia (Jurnal Bidan Cerdas, 2023)
Introduction: Postpartum women have several problems both physiologically and psychologically. Physiological changes during pregnancy often cause problems during the puerperium, one of which is skin problems, namely striae gravidarum. Purpose: To make Canira Malolo spread from Cacao, Virgin Coconut Oil, and aloe vera, and to know the Effectiveness of Canira Malolo against striae gravidarum in postpartum mothers in Polewali Mandar Regency. Methods: This study used a pre-experimental study design with the one group pre-test – post-test design. The sample size is 10 people using purposive sampling technique with inclusion criteria: Postpartum women who have striae gravidarum on the abdomen, have no history of oil allergies, have no open wounds and are willing to become research samples. Data analysis used the Wilcoxon Signed Ranks Test. The study was conducted in May – December 2022. Results: The results showed that Canira Malolo's intervention was effective in reducing the appearance of striae gravidarum in postpartum mothers with a p value=0.025. Conclusion: Canira Malolo made from cacao, virgin coconut oil, and aloe vera can be used as an alternative for treating Striae Gravidarum in postpartum mothers.